2011
DOI: 10.1149/1.3569994
|View full text |Cite
|
Sign up to set email alerts
|

Post-Test Characterization of an SOFC Short-Stack after 17,000 Hours of Steady Operation

Abstract: A typical F-design SOFC short stack of Forschungszentrum Jülich was metallographically analyzed after long-term steady-state operation for 17,000 h at 700°C and 0.5 A/cm². After scheduled shut down, the stack was partly embedded in resin and subsequently various stack parts were cut from multiple places of interest. All important components (cell, metal parts, sealant, and contact layers) were characterized with respect to microstructural and chemical changes and interactions with the adjacent components. Surp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 9 publications
4
29
0
Order By: Relevance
“…This indicates that the Cr species remained localized at the top of the cathode layer during cell operation as intended. From this result, it was concluded that the solid phase poisoning led to the same kind of Cr poisoning as reported in the literature for LSCF cathodes independent if they are used in real stack tests or single cell measurements (Menzler et al, 2011;Konysheva, 2014).…”
Section: Microstructural Analysissupporting
confidence: 73%
See 3 more Smart Citations
“…This indicates that the Cr species remained localized at the top of the cathode layer during cell operation as intended. From this result, it was concluded that the solid phase poisoning led to the same kind of Cr poisoning as reported in the literature for LSCF cathodes independent if they are used in real stack tests or single cell measurements (Menzler et al, 2011;Konysheva, 2014).…”
Section: Microstructural Analysissupporting
confidence: 73%
“…The amount of Cr 2 O 3 powder in the paste was calculated considering the wet layer thickness of the screen used for the screen printing process. It was targeted to achieve a Cr deposition, which is comparable to average Cr contents found in LSCF cathodes after several thousand hours of stack operation with JÜLICH specific stack design (∼100-200 µg cm −2 ) (Menzler et al, 2011;Beez et al, 2017). The Cr content of the paste was adjusted to 6.2 wt.-% (equals 0.1 g Cr 2 O 3 per 1 g organic matrix) with the aim to achieve a Cr deposition of ∼100 µg cm −2 .…”
Section: Experimental Paste Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9] Recently, a short stack achieved a 10 years lifetime, and remains in operation. 10 With proper protective coating, a voltage degradation rate of less than 0.3%/kh and lifetime of more than 40,000 h at 700…”
mentioning
confidence: 99%